Challenges in Distance Higher Education Amid the COVID-19 Pandemic - Domínguez Castillo, José Gabriel (2025)
The aim of this study was to examine the relationship between the domains of distance education and the variables of gender, Maya language, and university type, based on the perceptions of higher education students in urban and rural contexts. The study employed an observational, cross-sectional, and retrospective design with both descriptive and correlational scope. This approach was chosen to observe the variables of interest at a single point in time. The study is cross-sectional as it captures data at a specific moment, and retrospective because it relies on events that occurred prior to the investigation. Given the focus on determining the association between distance education domains and the aforementioned variables, a correlational analysis was applied. A non-probabilistic snowball sampling method was used due to the difficulties in accessing informants during the pandemic. The findings revealed significant gender differences in rural communities across all domains of distance education except for communication and interaction, with women consistently achieving higher scores. Furthermore, the domain of teacher attitude demonstrated the largest effect size, underscoring its crucial role in student development within virtual environments. To enrich these findings, further qualitative research is recommended to explore the challenges and achievements experienced by participants in their virtual learning journeys.